The Effect of Digital Literacy on Children’s Mental Development - Supardi; Salami Mahmud (TIFLUN : JURNAL PENDIDIKAN ANAK USIA DINI, 2024)
This research aims to explain the influence of poor literacy on children’s mental development and in self-disclosure through social media. The object of this research is the comments posted on the social networking site Facebook with the focus of the problem of elementary school students who upload intimate photos on Facebook. The formulation of the problems in this study are (1) what are the types of comments on the uploads of elementary school students who upload their intimate photos in the form of Memes. (2) How is the psychological impact of children on these comments? The research method used is qualitative research.The types of comments that appear in the subject of this study are ingratiation, intimidation, and supplication.The psychological impact of these comments on children is the tendency of children and adolescents to get used to insulting others, causing an envious attitude towards others, causing depression, being carried away by the mood of negative comments, and getting used to speaking with impolite language.